2018
DOI: 10.3354/meps12524
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and nitrogen zooplankton isoscapes in West Antarctica reflect oceanographic transitions

Abstract: Antarctic marine ecosystems are spatially and temporally dynamic. Regional climate change is significantly altering the patterns and magnitudes of this dynamism with cascading impacts on biogeochemistry, productivity, and food web architecture. Isoscapes (or isotopic maps) provide a valuable analytical framework to characterize ecosystem processes and address questions about trophic dynamics, animal movement, and elemental cycling. Applications of stable isotope methods to Antarctic ecosystems are currently li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 93 publications
3
40
0
Order By: Relevance
“…The δ 13 C and δ 15 N values of a consumer are the isotopic values of primary producers, the base of the food web, with modifications resulting from each trophic transfer, when energy is transferred from one trophic level to another (e.g. Lorrain et al 2009, Graham et al 2010, Jaeger et al 2010, Brault et al 2018. These modifications are predictable and described further below (Minagawa & Wada 1984).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The δ 13 C and δ 15 N values of a consumer are the isotopic values of primary producers, the base of the food web, with modifications resulting from each trophic transfer, when energy is transferred from one trophic level to another (e.g. Lorrain et al 2009, Graham et al 2010, Jaeger et al 2010, Brault et al 2018. These modifications are predictable and described further below (Minagawa & Wada 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Provided the primary processes driving variation are known, bulk δ 13 C values of an animal can give valuable information on its foraging habitat. The Southern Ocean is known to have considerable spatial variation in baseline δ 13 C (δ 13 C baseline ) values (Rau et al 1982, Quillfeldt et al 2010, Brault et al 2018. Several studies have observed decreasing δ 13 C values with increasing latitude, with offsets between about 55 and 79°S of approximately 3 ‰, largely reflecting variations in sea surface temperature (Rau et al 1982, Graham et al 2010, Quillfeldt et al 2010, Magozzi et al 2017, Brault et al 2018.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations